2000
DOI: 10.3109/hrp.8.5.261
|View full text |Cite
|
Sign up to set email alerts
|

Seclusion and Restraint: A Review of Recent Literature

Abstract: An October 1998 Hartford Courant investigative series highlighted alleged cases of brutality and death suffered by involuntarily secluded, restrained, and/or emergently medicated patients. The resulting public and professional furor prompted a spate of new federal regulations and legislative initiatives setting national standards for reporting and clinical oversight. These events provide stimulus for this literature review. Rates, duration, and methods of seclusion and restraint still vary widely. Little evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
89
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(102 citation statements)
references
References 53 publications
7
89
0
6
Order By: Relevance
“…Dangerous behaviours, towards oneself or others, and agitation or aggression are the most frequently cited reasons for SRU [1,3,4,11,23,27,30].…”
Section: Introductionmentioning
confidence: 99%
“…Dangerous behaviours, towards oneself or others, and agitation or aggression are the most frequently cited reasons for SRU [1,3,4,11,23,27,30].…”
Section: Introductionmentioning
confidence: 99%
“…Cet article examine cette interrogation de deux perspectives : d'une part, l'auteur tente de cerner ce qu'elle traduit de l'expérience des soignants, d'autre part il identifie les enjeux éthiques et juridiques des politiques des programmes de réduction des mesures d'isolement et de contention. (Busch et Shore, 2000), par la réduction de ces atteintes et par le développement des techniques de gestion de la violence les plus respectueuses possible. D'ailleurs, l'identification du problème n'est pas récente.…”
Section: Les Droits Du Patient : Une Menace Pour Les Soignants ?unclassified
“…Le « rapport de force » est donc nettement favorable au personnel soignant (Sjostrom, 2006). L'expérience historique (Busch et Shore, 2000) et la conscience vive que l'inégalité pave la voie aux abus (Kastrup, 2000) appellent une réponse éthico-juridique. Le consensus éthique et juridique (Seicshnaydre, 1992 ;Miller, 1997) est clair : il faut réduire au maximum l'usage de la force à l'égard des patients et minimiser les atteintes aux droits.…”
unclassified
“…p.159). Busch & Shore (2000) found that people with 'mental retardation' were more likely to experience restraint and seclusion than many other patient groups. However research on this subject with this population is limited.…”
Section: Secure Services For People With Learning Disabilitiesmentioning
confidence: 99%